2014
DOI: 10.1128/jvi.02163-14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Ebolavirus VP35 Suppression of Human Dendritic Cell Maturation

Abstract: Zaire ebolavirus (EBOV) VP35 is a double-stranded RNA (dsRNA)-binding protein that inhibits RIG-I signaling and alpha/beta interferon (IFN-␣/␤) responses by both dsRNA-binding-dependent and -independent mechanisms. VP35 also suppresses dendritic cell (DC) maturation. Here, we define the pathways and mechanisms through which VP35 impairs DC maturation. Wildtype VP35 (VP35-WT) and two well-characterized VP35 mutants ( IMPORTANCEThe VP35 protein, which is an inhibitor of RIG-I signaling and alpha/beta interferon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
81
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 36 publications
(79 reference statements)
1
81
1
Order By: Relevance
“…S1), suggesting that VP35 is a strong suppressor of innate immunity while the role of VP24 is more subtle. Interestingly, a recently published study demonstrated that plasmid-based delivery of VP35 to DC blocks TLR pathways only partially (57). However, unlike our work, this study did not involve infection of DC with live EBOV, which could result in greater levels of VP35 expression in infected DC.…”
Section: Discussioncontrasting
confidence: 51%
“…S1), suggesting that VP35 is a strong suppressor of innate immunity while the role of VP24 is more subtle. Interestingly, a recently published study demonstrated that plasmid-based delivery of VP35 to DC blocks TLR pathways only partially (57). However, unlike our work, this study did not involve infection of DC with live EBOV, which could result in greater levels of VP35 expression in infected DC.…”
Section: Discussioncontrasting
confidence: 51%
“…Replication-defective lentiviruses were generated as previously described (31,35). Expression plasmids used were pHCMV-G encoding VSV glycoprotein, packaging plasmid pNL4.3-gagpol and derivatives of pHR-SIN-CSIGW.…”
Section: Isolation Of Human Mddcs and Naive T Cells Human Mddcs Werementioning
confidence: 99%
“…These observations are likely relevant to in vivo infection since DCs have been demonstrated to be targets of infection in animal models and in infected humans. EBOV IFN-antagonist proteins have been implicated as potentially mediating this suppression (28)(29)(30)(31). Expression of eVP35 in monocyte-derived DCs (MDDCs) is sufficient to disrupt not only IFN-␣/␤ production but also production of proinflammatory cytokines, upregulation of cell surface expression of DC maturation markers, and activation of T cells following infection of the cells with RIG-I activator Sendai virus (SeV) or MDA5 activator encephalomyocarditis virus (EMCV) (31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to VP35's critical role in virus replication as a cofactor of the viral polymerase, it has also been extensively studied for its function in inhibition of innate signaling pathways and expression of antiviral type I interferons (IFN-I) (10,11,(14)(15)(16)(17)(18)(19)(20). VP35 also inhibits the maturation of dendritic cells (DCs) and prevents efficient adaptive immune responses (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%